PENGARUH ENVIRONMENTAL, SOCIAL, GOVERNANCE (ESG) DISCLOSURE , KEPEMILIKAN ASING, DAN KEPEMILIKAN INSTITUSIONAL TERHADAP NILAI PERUSAHAAN (Studi Empiris pada Perusahaan Sektor Manufaktur Berdasarkan Klasifikasi IDX-IC yang Terdaftar di Bursa Efek Indonesia Tahun 2022-2024) - Vinia Putri Nikita Nasution; Etna Nur Afri Yuyetta (Diponegoro Journal of Accounting, 2026)
This study aims to analyze the effect of Environmental, Social, Governance (ESG) Disclosure, foreign ownership, and institutional ownership on firm value in manufacturing companies listed on the Indonesia Stock Exchange for the period 2022–2024. Firm value is measured using Tobin’s Q, ESG Disclosure is measured using the Bloomberg ESG Disclosure Score, while foreign ownership and institutional ownership are measured as a percentage of shares held relative to total outstanding shares. This study employs a quantitative approach using secondary data obtained from the Indonesia Stock Exchange and Bloomberg database. The sample was determined through purposive sampling, yielding 73 companies with a total of 219 observations. The analysis method used is panel data regression with the Common Effect Model, selected based on the Chow Test and Lagrange Multiplier Test using EViews 12. The results show that ESG Disclosure has a positive and significant effect on firm value. Institutional ownership has a positive and significant effect on firm value. Meanwhile, foreign ownership does not have a significant effect on firm value. The Adjusted R-squared value of 54.49% indicates that the three independent variables substantially explain the variation in firm value.